PERBANDINGAN METODE SHOW AND TELL DAN METODE PEMBELAJARAN BERBASIS RISET BESERTA PRESENTASI TERHADAP KETERAMPILAN BERBICARA PADA SISWA SMAN 3 PAMEKASAN - Naila Imtiyaz Mufid; Muchlis Sholichin; Muhamad Arifin Alatas (Journal of Education Partner, 2023)
This article aims to determine the influence of the show and tell method on students' speaking skills at SMAN 3 Pamekasan and to find out how much influence the show-and-tell method and research-based methods and presentations have on students' speaking skills. The research approach used is a quantitative approach with an experimental research type and uses a between-subjects research design. The population in this study were students in classes X-A and X-C at SMAN 3 Pamekasan. The sample used is cluster sampling because this sample examines students in groups containing 6 people in each group. Data collection techniques use practical tests, documentation, and student work results. These two learning methods received an average score of 21.3 for the research and presentation method, and 17.4 for the show-and-tell method. The results of this research prove that, firstly, there is no influence on the use of the show-and-tell method on speaking skills in class X-A students at SMAN 3 Pamekasan. This is proven by using the t-test. In this test, the account value was found to be 4.9, while the resulting table value was 2.1447. From the results obtained from the t-test formula used, it is proven that H0 is rejected and Hi is accepted with a significance level of <0.05. Second, how much influence does the show-and-tell method have on students' speaking skills? In this case, the show-and-tell class gets a percentage of 18%, while the research and presentation-based class gets 20% for speaking skills.